Social Function of Land in The Development and Acquisition of Land For Public Interest - Arvid Syahbuddin Januar; Faizatuluzmi Mardhiana; Amalia Anggita Cahyani; Titi Aisyah Dhaniarni (IHSA Institute, 2022)
This study examines aspects of the social function of land for the public interest in every development carried out by the government. Second, how is the polemic in the compensation process for relinquishing land rights for development. Finally, the polemic of the Constitutional Court's decision no. 50/PUU-X/2012. The research findings show that the conception of the Social Function of Land for the public interest is not always in accordance with the real meaning of the public interest and the process of compensation for land is still far from the spirit of the UUPA Jo Article 33 of the 1945 Constitution. 2/2012, to deconstruct the meaning of “social function of land” in order to conform to the philosophy of Article 33 of the 1945 Constitution and the LoGA. The DPR must immediately complete the Agrarian Structure Reform and Restructuring Bill, the Agrarian Conflict Resolution Bill, and the Natural Resources Management Bill, as mandated by MPR Decree No. IX/2001 Jo Tap MPR No. V/2003. Development for the public interest must be placed in the spirit of the social function of land and agrarian reform in order to achieve the greatest prosperity for the people.